Women osteoporosis prevention by protein, fat, vitamin D, phosphorus intake and chicken feet cookies consumption as source of calcium - Rahma Ayu Ramadhania; Adi Magna Patriadi Nuhriawangsa; Lilik Wijayanti (AcTion: Aceh Nutrition Journal, 2024)
Osteoporosis as a major health problem has four times risk in women than men. Protein, fat, vitamin D, and phosphorus are the main nutrients in bone development. Through this study, it can be known protein, fat, vitamin D, and phosphorus changes from the consumption of cookies chicken feet flour (Gallus domesticus), containing 130 mg calcium, equivalent to 15% of  RDA to prevent osteoporosis due to low calcium intake with a quasi-experimental pre-test and post-test approach with control in women early adulthood for 14 days in Health Office of Tasikmalaya District in June 2022, with 102 people as sample based on Slovin's calculation with 10% of margin error through the multistage sampling method, which consists of cluster random sampling and simple random sampling. Observation of protein, fat, vitamin D, and phosphorus using the semi food frequency questionnaire. Data analysis used Post Hoc LSD. Based on data analysis, it is known that the difference in protein, vitamin D, and phosphorus intake significantly different with p> 0,05 of the three groups each other. While the difference in fat intake significantly different from the positive and negative control groups with p> 0,05. Consumption of cookies can increase protein, fat, vitamin D, and phosphorus intake.